The Relation of Students Knowledge About Potential Chemical Hazards with Work Accidents in the Chemistry Laboratory of the Department of Nutrition, Health Polytechnic, Ministry of Health, Palangka Raya - SY, Yetti Wira Citerawati; Hidayatulloh, Agus; Sukrianur, Ahmad (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
A chemistry laboratory is a place that has the potential to pose a danger to students during practicum. One factor that influences the incidence of work accidents in educational laboratories is student knowledge, especially about potential chemical hazards. This study aims to determine the relationship between students’ knowledge about potential chemical hazards With Accident events Work In The Chemistry Laboratory Of The Department Of Nutrition, Health Polytechnic, Ministry Of Health, Palangka Raya. This research is a type of quantitative research, the analytic observation method with a cross-sectional design. Sampling using a total sampling technique. The instrument for measuring knowledge and the incidence of work accidents is in the form of a questionnaire and has been tested for validity and reliability. The data obtained were analyzed by chi-square test with a significance level of 95%.  The sample in this study was 73 respondents 17-24 years old with a gender distribution of 9 (12%) males and 64 (88%) females. The range of knowledge scores is a minimum of 25 and a maximum of 90, the median is 70 and the mean is 67.4. The level of knowledge is 40 (54.8%) good and 33 (45.2%) less. Based on the results of the study, as many as 26 respondents (35,6%) had experienced work accidents and as many as 47 respondents  (64.4%) had never had work accidents. The chi-square statistical test results showed no relationship between student knowledge of potential chemical hazards and accident events in chemistry laboratories. The conclusion of this research is that there was not a relationship between student knowledge of potential chemical hazards with accident events Work in chemistry laboratories of the Nutrition Department of the Health Polytechnic of the Ministry of Health, Palangka Raya. Further research should be carried out regarding other variables that influence the incidence of work accidents in chemical laboratories.